Centralizing EU Policy in Fighting Infectious Diseases: Status Quo, Citizen Preferences, and Ways Forward - Roel Beetsma; Brian Burgoon; Francesco Nicoli; Anniek de Ruijter; Frank Vandenbroucke (CESifo Forum, 2020)
We confront the traditional role of the EU in the domain of health with the urgent need for collective action triggered by the coronavirus pandemic. In the face of such a crisis, we argue that the joint procurement, stockpiling, and allocation of medical countermeasures is a key component of true European solidarity, besides maintaining the integrity of the single market. We present the first results of a survey experiment taken before the current crisis on citizens' attitudes toward centralizing at the EU level of policies to combat infectious diseases, which indicates considerable support.
Keywords: 330